(untitled) (Portuguese Journal of Family Medicine and General Practice, 2023)
Legacy has to do with everything that is built and transmitted to others, and which, due to its importance, remains current, allowing it to perpetuate itself from generation to generation over time and transforming others’ lives, others’ contexts, others’ realities, with a purpose that can be useful to others. Vasco António de Jesus Maria was born in Pombal on May 1, 1955, and his life path as a man and as a doctor leaves essence, value, and vision that is eternal.